Rational Design of Self-Healing Tough Hydrogels: A Mini Review - Wang, Wenda; Narain, Ravin; Zeng, Hongbo (Frontiers in Chemistry, 2018)
Hydrogels are three-dimensional cross-linked polymer networks which can absorb and retain large amount of water. As representative soft materials with tunable chemical, physical and biological properties, hydrogels with different functions have been developed and utilized in a broad range of applications, from tissue engineering to soft robotics. However, conventional hydrogels usually suffer from weak mechanical properties and they are easily deformed or damaged when they are subjected to mechanical forces. The accumulation of the damage may lead to the permanent structural change and hence the loss of the functional properties of the hydrogels. Therefore, it is important to develop mechanically robust hydrogels with autonomous self-healing property in order to extend their lifespan for various applications. In this mini review, we present current strategies for synthesizing self-healing and tough hydrogels respectively and some recent examples are highlighted. We conclude with a perspective on the remaining challenges in the field as well as the recommendations for future development.